Thermal effect of energy producing equipment on the deterioration of fire-resistants and elimination of erosion products into the environment - Abraitis, R.; Abraitis, D. (Видавництво Національного університету «Львівська політехніка», 2007)
The development of energy production caused by the evolution of modern industry is closely related with the intensification of technological processes. Since the exploration of the process of surface erosive deterioration that takes place in the flows of combustion products has acquired a larger scale, it is urgent to examine the phenomena that emerge in erosites, on the surfaces of Al2O3, MgO, and ZrO2. On the basis of the data found in scientific literature and results obtained during the high-temperature speedy experiments with the ceramic materials it would be purposeful to intoduce adequate corrections into the estimatio system of environmental pollution.